Welfare dynamics in India over a quarter-century: Poverty, vulnerability, and mobility, 1987-2012 - Hai-Anh H. Dang; Peter Lanjouw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We analyse the Indian National Sample Survey data spanning the period 1987/88-2011/12 to uncover patterns of transition into and out of different classes of consumption distribution. At the aggregate level, income growth has accelerated, accompanied by accelerating poverty decline. Underlying these trends is a process of mobility, with 40-60 per cent of the population transitioning between consumption classes, and increasing mobility over time. Yet the majority of those who escape poverty remain vulnerable. Most of those who are poor were also poor in the preceding period, and are thus likely to be chronically poor. The characteristics of upwardly mobile households contrast with those of the poor; these households are also far less likely to experience downward mobility. While mobility patterns are heterogenous across states, within-state trends are qualitatively similar to national trends.
Keywords: C15; I32; O15; 330; intragenerational mobility; welfare dynamics; imputation; synthetic panel; India; National Sample Survey